Model Penyelenggaraan Keaksaraan Dasar Melalui Pelibatan Tokoh Agama - Ilmar Andi Achmad; Muhammad Athar Asmas; Yusril Arib (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
The product development model for literacy education will be used by tutors who are religious leaders to students to reduce illiteracy in West Sulawesi, especially Mamasa Regency based on the Education and Culture Statistics Data Center (2018), West Sulawesi Province is included as six provinces with the highest percentage of illiterates or in the red zone. Illiteracy at the age of 15-59 years in West Sulawesi Province, which reached 36,124 people or 4.360%. While the highest regency, namely Majene Regency, amounted to 9.30%. Followed by the second highest Pasangkayu Regency, 7.43%, and the third highest Mamasa Regency, 6.37%. While the lowest regency, namely Polman Regency, 1.57%, the second lowest Mamuju Regency, 2.68%, and the third lowest Central Mamuju Regency, for this model it is very important to use. The development of this model contains the results of the implementation of research and model development, starting from the preliminary study activities, validation of the conceptual model by experts, experts and practitioners and the results of the trial of the conceptual model and the results of the trial of the operational model. The implementation of basic literacy programs in Mamasa Regency is not much different from other regions, where most of the programs are implemented by PKBM and SKB with funding sources using BOP from the Directorate of Literacy and Equality Education Development (Dit. Bindiktara). While financial support for the implementation of basic literacy programs from local governments (APBD) is very rare. Based on Education Basic Data (2019) the number of PKBM in Mamasa Regency reached 30 units and 1 SKB. A number of these institutions should be able to reduce the high illiteracy rate, because one of the main programs is basic literacy. In addition, BOP assistance was provided from the government, but the implementation of the basic literacy program has not yet achieved the expected results. Keywords: KD Model, Religious Figure.